Lessons from the British and French new towns : paradise lost? - Fée, David; Colenutt, Bob; Coady Schäbitz, Sabine (Bingley, U.K. : Emerald Publishing Limited, 2020)
Lessons from the British and French New Towns: Paradise Lost? explores the evolution of the New Towns in both France and the UK from several perspectives including public policy, sociology, geography and heritage. UK and French New Towns have many similarities in terms of the role of the national state in tackling urgent problems of housing and urban growth and in promoting innovative design and architecture. These innovative planned settlements have left a contested and complex legacy, but are once again on the political and urbanisation agenda in Europe, where a push for growth of housing and the desire for sustainability are the new drivers of urban planning and design. After years of the private development market being seen as the principal instrument of urban growth and planning, it is time to assess the urban legacy and the heritage of the UK and French New Towns. This book contrasts their evolution on both sides of the Channel and shows what can be learned about post war state planning and the future planning of new settlements.
Prelims -- Lessons from British and French New Towns: Paradise Lost? -- Part I: The New Towns and Policymakers -- Chapter 1: Reinventing the Healthy Garden City: Ebbsfleet's Learning from the New Towns -- Chapter 2: Loss and Longing: Whatever Happened to the Egalitarian Ethos of the UK New Towns? -- Chapter 3: Unpacking the Official View: Five Myths on British New Towns -- Chapter 4: Beyond Your Wildest Dreams? Building New Towns in France Today -- Part II: The New Towns and Their Residents -- Chapter 5: Ways of Knowing the Landscape of the New Towns: A Lefebvrian Analysis -- Chapter 6: The Suburban Urbanity of the New Towns: Everyday Life in Cergy-Pontoise and Milton Keynes -- Chapter 7: Saint-Quentin-en-Yvelines: Lessons Learned from the Years 19652019 -- Part III: The New Towns in their Wider Regional and International Context -- Chapter 8: The London New Towns in Their Changing Regional Context -- Chapter 9: Planning the World's New Towns A Tale of Two Countries, 19752013 -- Chapter 10: Learning from the Contrasting Histories and Trajectories of Harlow and Thamesmead -- Part IV: The New Towns and Heritage -- Chapter 11: Public Art in British New Towns: The Past, Present and Future -- Chapter 12: Public Art in French New Towns: From Experiments to Heritage -- Chapter 13: A Tangible Utopia: The Genesis of Built Experiments in French New Towns -- Chapter 14: A Controversial Heritage: New Towns and the Problematic Legacy of Modernism -- Conclusion -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: City planning; Urban policy; Social Science -- Sociology -- Urban; Urban & municipal planning